Pembinaan Prestasi Olahraga Atletik di Kabupaten Kendal Tahun 2019 (Indonesian Journal for Physical Education and Sport, 2021)
Aim of this study is to determine the implementation of installation, breeding, and coaching in the athletic sports achievement at PASI Kendal Regency. This study used a qualitative approach research method. The subjects of this study were administrators, coaches and athletes. The techniques of collecting data in this study were through observation, interviews, and documentation. The techniques of analyzing data used data collection, data reduction, and drawing a conclusion. The validity of the data in this study used data triangulation. The results showed that the stages of installation and breeding in the athletic sports at PASI Kendal Regency were carried out by introducing athletic sports during open selection activities or through direct observation towards the school. The athletic sports PASI in Kendal Regency have quite good achievements because they are supporting by infrastructure, a qualified trainers who have Level 3 IAAF certificates, and there are intensive and extra for outstanding athletes. The conclusion of this study is the development of athletic sports achievement in PASI Kendal Regency year 2019 included as good criteria